2021
DOI: 10.36227/techrxiv.15097545.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical Modelling of Dielectric Modulated Negative Capacitance MoS2-FET for Biosensor Application

Abstract: In this paper, a dielectric modulated negative capacitance (NC)-MoS<sub>2</sub> field effect transistor (FET)-based biosensor is proposed for label-free detection of biomolecules such as enzymes, proteins, DNA, etc. Various reports present experimental demonstration and modelling of NC-MoS<sub>2</sub> FET, but it is never utilized as a dielectric modulated biosensor. Therefore, in this work, the modelling, characterization and sensitivity analysis of dielectric modulated NC-MoS<sub&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…So the DM-TFET biosensor suppress the difficulties faced by the CFET biosensor in terms of sensitivity, response time, power consumption. The superior characteristics of the DM-TFET biosensors attracted many researchers to carry out immense research in this field and reported impressive statistics device sensitivity [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The low on current (I on ) and ambipolar conductivity are the two stumbling blocks for achieving high performance for TFET devices, so the device is not recommended for digital applications.…”
Section: Introductionmentioning
confidence: 99%
“…So the DM-TFET biosensor suppress the difficulties faced by the CFET biosensor in terms of sensitivity, response time, power consumption. The superior characteristics of the DM-TFET biosensors attracted many researchers to carry out immense research in this field and reported impressive statistics device sensitivity [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The low on current (I on ) and ambipolar conductivity are the two stumbling blocks for achieving high performance for TFET devices, so the device is not recommended for digital applications.…”
Section: Introductionmentioning
confidence: 99%